Test-retest repeatability for Fatigue Assessment Scale, Short-Form 6-Dimension and King’s Sarcoidosis Questionnaire in people with sarcoidosis associated fatigue. - Ferris, Rebecca; Maung, Tun; Atkins, Christopher; Terrington, Dayle; Clark, Allan; Manivarmane, Surya Prasad; Wilson, Andrew (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background and aim: Patient related outcomes are important in sarcoidosis but the medium-term repeatability of the key patient reported outcome measure is not known. We aimed to test the repeatability of the Fatigue Assessment Scale (FAS), Short Form 6-Dimension (SF-6D), and King’s Sarcoidosis Questionnaire (KSQ) in free living people with sarcoidosis associated fatigue. Methods: Twelve people with sarcoidosis associated fatigue completed the FAS, short form 36 questionnaire (SF-36) and the KSQ at baseline and 12 weeks. The SF-6D utility was calculated from the SF-36. The difference between baseline and 12 week assessments was measured. Results: The interclass correlation (95% confidence interval) showed good agreement between the baseline and 3 months measurements: FAS 0.91 (0.74, 0.71), SF-36 0.98 (0.94, 1), KSQ 0.98 (0.93, 0.99), SF-6D utility 0.98 (0.93, 0.99). The baseline (standard deviation) FAS was 27.83 (5.86) and at 12 weeks was 27.25 (7.55) representing 0.58 difference (95% CI for difference (-1.89, 3.06)), SF-6D utility was 0.69 (0.16) at baseline and 0.68 (0.17) after 3 months representing at 0.00 (-0.03, 0.03) difference and corresponding values for KSQ were 59.12 (18.68) and 56.91 (27.26) with a difference of -1.87 (5.49,1.76). Conclusions: There was good repeatability of FAS, SF-36, SF-6D and KSQ in free living people with sarcoidosis associated fatigue. Fatigue, general and disease specific health related quality of life showed no significant change over a 12 week period. Studies identifying changes in these outcomes can confidently report a true change and not measurement error or regression to the mean.